Implementasi Membaca Kitab Turos bagi Alumni di Pesantren Nizhomul Hikmah Desa Tamiang Kec. Batang Lubu Sutam Kab. Padang Lawas - Nasution, Nazifah Ramadani (TSAQOFAH, 2023)
Studying the turos book is a necessity in order to understand Islamic teachings comprehensively. However, the study of the turos book today is of little interest. Not only in society and public schools, but also among Islamic boarding schools is not an urgent matter anymore. In addition, to be able to understand monotheism, fiqh, tasawuf, interpretation, hadith and others, one must be able to read and understand the turos books which are the legacy of the previous scholars. The way to be able to read and understand the book of turos is to study the rules of Arabic grammar such as nahu, nerves, balaghah, mantiq and others. Nevertheless, it does not mean that there are no more Islamic boarding schools that study how to read the turos book. There are still a number of Islamic boarding schools that are still consistently studying the turos book. One of them is the Nizhomul Hikmah Islamic Boarding School in Tamiang Village, Kec. Batang Lubu, Sutam Regency. PadangLawas. Therefore, the author is interested in discussing how to implement reading the book of turos for alumni at the Nizhomul Hikmah Islamic Boarding School. This study uses a qualitative method. This research includes field research in order to obtain valid and representative data. Based on the research conducted, it can be interpreted that the implementation of reading the turos book for alumni at the Nizhomul Hikmah Islamic Boarding School is learning the turos book with the classical method where the teacher conveys the study and the students only listen to what is conveyed, as well as the method of memorizing each vocabulary with the emphasis on the importance of learning nahu and nerves as the main route to be able to read the book of turos.